1996
DOI: 10.2527/1996.7492187x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of realimentation of mature cows on maturity, color, collagen solubility, and sensory characteristics.

Abstract: Cull beef cows (n = 80) that had consumed similar grassland diets were assigned to one of four feeding periods (0, 28, 56, and 84 d) and subdivided into two groups fed either a high-energy, high-protein diet or a high-energy, low-protein diet. Treatments were designed to examine the effect of time on feed, dietary protein, and electrical stimulation on carcass traits, composition, shear force, sensory profile, collagen characteristics, and myoglobin state. Within 1 h of slaughter, the right side of each carcas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
2
9

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 15 publications
6
33
2
9
Order By: Relevance
“…Boleman et al (1996) found that cull cows, fed for 84 days showed lower amount of connective tissue than cows fed 0, 28 or 56 days, and this proves that the intensive pre-slaughter feeding causes increased levels of soluble collagen. In addition, there was an increase in juiciness and palatability of meat.…”
Section: Resultsmentioning
confidence: 77%
“…Boleman et al (1996) found that cull cows, fed for 84 days showed lower amount of connective tissue than cows fed 0, 28 or 56 days, and this proves that the intensive pre-slaughter feeding causes increased levels of soluble collagen. In addition, there was an increase in juiciness and palatability of meat.…”
Section: Resultsmentioning
confidence: 77%
“…A maciez média dos três pesos de abate foi de 6,77 pontos, superior ao relatado para animais desta categoria de idade (Restle et al, 1999). Segundo Boleman et al (1996), a alimentação de animais no período de terminação com dieta de elevada densidade energética favorece as características sensoriais da carne, inclusive a maciez, em função da rápida síntese de proteínas, aumentando a proporção de colágeno solúvel na carne, o que provavelmente ocorreu no presente experimento dado ao elevado ganho de peso (Arboitte et al, 2004).…”
Section: -Very Coarse; -Coarse; 3 -Light Coarse; 4 -Fine; 5 -Very Funclassified
“…Most of the current literature examining cattle fed diets of differing energy levels focuses on the m. longissimus dorsi. Boleman et al (1996) reported that longissimus WBS values significantly decreased after cull cows were on a concentrate diet for 56 d, whereas Faulkner et al (1989) reported a decrease in cull cow loin shear force after 42 d on feed. Cranwell et al (1996a) also reported a decrease in loin shear force after 28 d on concentrate but did not observe any further decreases.…”
Section: Warner-bratzler Shear Forcementioning
confidence: 99%
“…Feeding high-energy diets to cull cows before slaughter has the ability to improve the quality grade by 2 primary factors: LMAT scores tended to decrease and MARB tended to increase. Lean maturity scores could be improved by producing a brighter lean (Miller et al, 1987;Boleman et al, 1996;Cranwell et al, 1996a) and firmer, finer textured lean (Brown and Johnson, 1991).…”
Section: Carcass Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation